Hiring Cheerleaders: Board Appointments of “Independent” Directors - Cohen, Lauren; Frazzini, Andrea; Malloy, Christopher J. (Management Science, 2012)
We provide evidence that firms appoint independent directors who are overly sympathetic to management, while still technically independent according to regulatory definitions. We explore a subset of independent directors for whom we have detailed, microlevel data on their views regarding the firm prior to being appointed to the board: sell-side analysts who are subsequently appointed to the boards of companies they previously covered. We find that boards appoint overly optimistic analysts who are also poor relative performers. The magnitude of the optimistic bias is large: 82.0% of appointed recommendations are strong buy/buy recommendations, compared with 56.9% for all other analyst recommendations. We also show that appointed analysts' optimism is stronger at precisely those times when firms' benefits are larger. Last, we find that appointing firms are more likely to have management on the board nominating committee, appear to be poorly governed, and increase earnings management and chief executive officer compensation following these board appointments. This paper was accepted by Brad Barber, finance.